Construction materials : their nature and behaviour - Domone, P. L. J.; Illston, J. M. (Spon Press, 2010)
Covers various developments of Construction Materials such as the use of glass as a structural material. This work examines the contribution that material selection makes to sustainable construction practice, considering the availability of raw materials, production, recycling and reuse, which contribute to the life cycle assessment of structures.